-(z+7)+(6z+1)=-4(z+1). What is the soultion

Question

Asked 2/11/2013 12:22:57 PM

Updated 2/12/2014 7:52:13 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [2/12/2014 7:49:00 PM]

Expert answered|Salihahptc|Points 10|

Question

Asked 2/11/2013 12:22:57 PM

Updated 2/12/2014 7:52:13 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [2/12/2014 7:49:00 PM]

Rating

3

-(z+7)+(6z+1)=-4(z+1)

-z - 7 + 6z + 1 = -4z - 4

5z - 6 = -4z - 4

5z + 4z = -4 + 6

9z = 2

z = 2/9

The solution is 2/9.

-z - 7 + 6z + 1 = -4z - 4

5z - 6 = -4z - 4

5z + 4z = -4 + 6

9z = 2

z = 2/9

The solution is 2/9.

Added 2/12/2014 7:52:13 PM

This answer has been confirmed as correct and helpful.

Solove the solution. User: SOlve the solution z=what. 5(3z-1)-4(z+2)=6(z+1)

Question

Not Answered

Updated 4/26/2014 11:12:28 AM

1 Answer/Comment

5(3z-1)-4(z+2)=6(z+1)

15z - 5 - 4z - 8 = 6z + 6

11z - 13 = 6z + 6

11z - 6z = 6 + 13

5z = 19

z = 19/5

15z - 5 - 4z - 8 = 6z + 6

11z - 13 = 6z + 6

11z - 6z = 6 + 13

5z = 19

z = 19/5

Added 4/26/2014 11:12:28 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/26/2014 1:37:52 PM]

Solve the equation and solve the solution? 5(3z-1)-4(z+2)=6(z+1) The solution is z=? **Weegy:** 5(3z-1)-4(z+2)=6(z+1),
11z-13=6z+6,
11z - 6 = 6 + 13,
5z = 19, The solution is z = 19/5 (More)

Question

Expert Answered

Updated 6/19/2014 10:40:12 PM

0 Answers/Comments

27,082,830

questions answered

There are no comments.